(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
The infinitive forms of the Church Slavonic language of Ukrainian edition of the end of XVI – XVII centuries are analyzed in the article, comparative analysis of the structural features of these forms with respective ones in the Old Church Slavonic language and Ukrainian XVI - XVII centuries conducted.